Perceptual span, visual span, and visual attention span: Three potential ways to quantify limits on visual processing during reading - Frey, Aline; Bosse, Marie-Line (Visual cognition, 2018)
Many lines of evidence have revealed limitations of the human visual system, most notably that only a portion of available information is processed in a single glance. A degree of conceptual confusion has emerged, however, regarding the underlying concepts or mechanisms explaining limited visual processing in reading; perceptual span, visual span, or visual attention span. While the original definitions of these three concepts are clear and well-differentiated, they are routinely used inconsistently in the literature. The primary goal of the present review is to re-specify these three concepts in terms of what they correspond to and how they are determined. Further, we investigate whether these three spans refer to vision-related measurements and/or are based on general cognitive abilities. This review should lead to a better understanding of the involvement of visual functions in reading performance.